If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9x+5=8x+9
We move all terms to the left:
-9x+5-(8x+9)=0
We get rid of parentheses
-9x-8x-9+5=0
We add all the numbers together, and all the variables
-17x-4=0
We move all terms containing x to the left, all other terms to the right
-17x=4
x=4/-17
x=-4/17
| x^2+10x-26=3x+4 | | 5y-27=29 | | 12x/3=6 | | 5+(2x-3)=x-(3x+10 | | 4(y-2)=2y-+6 | | 9=4(c-2)= | | 7(4x-9)-5=16 | | 3x-7=14x-62 | | 4x+3=19-6x | | −9+7x=−2x+108 | | 13.65=4.88+h | | x×8=48 | | 4(2x-5)=5x | | a÷6=6 | | 4-81x²=0 | | 20+2x=6+9 | | 3x-2(3x-2)=5+1(x+3) | | 2t+1=5t−12.5 | | 2x+7=£x-12 | | -24x=36 | | 12+x=(16-70x) | | 3x(2x-1)=4x-9 | | x+1/5=1/5x-3 | | 60-4a=5-8a | | 11n+25=6n | | 2*(x-4)+1=6x | | 5b+5=4b+8 | | 2(5x-3)+3=3(2x-1)+4x | | 1/2(2x-3)+1/3(x+1)=1/2(3x-1) | | 31-2a=36-9a | | 2y+4/2=3 | | (x-5)+((x+1)2)=36 |